Studies on the potential recovery of copper from low-grade mixed sulfide-oxide ore and optimization of the process parameters. Issue 5 (24th March 2022) - Harichandan, Barun; Mandre, N.R.
ABSTRACT: The authors attempted to investigate the copper recovery possibilities from low-grade mixed sulfide-oxide ore in the present paper. The randomized leaching experimental results in sulfuric acid solution are further used to develop a statistical model for predicting the copper recovery. Identifying the factors that control the dissolution process is critical for enhancing the rate of copper recovery from this low-grade ore, and this article is completely focused on that aspect. Herein, Box-Behnken design (BBD) of response surface methodology with three factors at three levels is applied to predict the optimum copper recovery value. The regression analysis (R 2  = 99.9%) result suggested that the predicted values are highly consistent with experimental values. The F-test and ANOVA results indicated that time, temperature factor, and particle size affected the copper recovery significantly. So, a maximum of 87% copper can be recovered at the selected condition of leaching time: 120 minutes, temperature: 90°C, particle size: 63 µm, stirring speed: 400 rpm, solid-liquid ratio: 1:5 (gm/ml), and acid concentration: 1 M, which is close to the value of 88.07% predicted by the statistical design model. Therefore, the copper recovery values obtained from the model are well in agreement with the experimental values.